MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR PESERTA DIDIK MELALUI PENERAPAN STRATEGI PEMBELAJARAN IDEAL PROBLEM SOLVING PADA POKOK BAHASAN KELARUTAN DAN HASIL KALI KELARUTAN DI KELAS XI MIA 1 SMAN 2 PEKANBARU - Claudia Oktaviani; Roza Linda; Johni Azmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : The aim of this research was to improve the student activity and achievement used IDEAL problem solving strategy on solubility and solubility product subject at XI MIA 1 of Senior High School (SMAN) 2 Pekanbaru in academic year 2016/2017. This research was an action research with two cycle design. Each cycle consisted of two meetings included four stages of implementation: planning, action, observation, and reflection. The collecting data used observation and test. The analysis data was describ with descriptively. The result of action showed that learning activity percentage of student improved and reached the success criteria. The learning activity of student percentage in first cycle was 55,56% with enough category and the second cycle was 66,7% with good category. Student achievement was seen from mastery learning that enhances and have achieved success criteria. The percentage of student achievement in the first cycle was 80,48% and the second cycle was 90,24%. Based on the results obtained, it can be concluded that using IDEAL problem solving strategy can improve the activity and student achievement.Keyword: IDEAL problem solving strategy, student learning activity, student achievement